Plant Sterols and Metabolic Health: Current Evidence on Insulin Resistance and Type 2 Diabetes Mellitus - Partha Deb Roy; Vadivelan Ramachandran; Tharani M; Kalirajan Rajagopal; Venkatesh Gunasekaran; Ruchı Tıwarı (Hacettepe University Journal of the Faculty of Pharmacy, 2026)
Plant sterols are naturally occurring bioactive compounds widely recognized for their cholesterol-lowering effects. This narrative review critically evaluates current evidence regarding the role of phytosterols in insulin resistance, glucose metabolism, and type 2 diabetes mellitus (T2DM). Literature was collected from PubMed, Scopus, and Google Scholar for studies Published between 2000 and 2024 using pre-defined keywords related to phytosterols, insulin resistance, and T2DM. Evidence from in-vitro and animal studies suggests that phytosterols may influence AMPK, PI3/Akt, and GLUT4 signaling pathways and may improve metabolic homeostasis. However, evidence from human clinical trials remains limited and in-consistent. Current findings strongly support the lipid-lowering benefits of phytosterols, where as their role in glycemic control requires further validation through well-designed clinical studies.